Functional–Metabolic Continuum: A Novel Perspective on the Pathogenesis of Stress-Induced Metabolic Disorders. A problem-oriented review - Gozhenko, Anatoliy; Zukow, Walery; Gozhenko, Olena; Pavlega, Hanna; Popovych, Igor (Pedagogy and Psychology of Sport, 2025)
Background: The global epidemic of metabolic diseases demands novel theoretical frameworks for understanding their pathogenesis. The functional–metabolic continuum (FMC) concept, first articulated by Gozhenko in 2010, offers an integrative model connecting stress physiology, metabolic regulation, and cardiovascular disease. Objective: To present a comprehensive review of the FMC concept—its evolutionary foundations, pathophysiological mechanisms, clinical manifestations, and therapeutic implications—with particular emphasis on the standardized regulatory–metabolic response that evolved to support physical function. Key Concepts: The FMC postulates that health depends on temporal and quantitative coupling between metabolic mobilization of energy substrates by neuroendocrine systems and their utilization by somatic functions, especially muscular activity. Evolution shaped a standardized regulatory–metabolic response—uniform in direction and magnitude—that was inseparably linked with physical function. This response is stereotypical and cannot be flexibly downregulated; regulatory activation invariably produces standard metabolic mobilization, regardless of whether physical activity will actually occur. Modern conditions disrupt this coupling via two principal mechanisms: (1) psychoemotional stress activates neuroendocrine systems and mobilizes substrates in the ancestral "fight-or-flight" pattern, yet social constraints prevent the physical activity that would consume these substrates; (2) dietary excess supplies substrates in quantities chronically exceeding utilization capacity, especially when combined with sedentary lifestyles. Both mechanisms result in chronic or recurrent hyperglycemia and hyperlipidemia, damaging vascular endothelium through glycosylation, oxidative stress, inflammation, and lipid accumulation. Endothelial dysfunction represents the central pathogenetic link between metabolic derangements and clinical cardiovascular disease. Our studies of circulating desquamated endothelial cells demonstrate progressive endothelial damage across a continuum—from apparently healthy individuals through isolated arterial hypertension and ischemic heart disease to comorbid states—correlating with the severity of metabolic disturbance. Therapeutic Implications: Restoration of the FMC through physical activity (consumption of mobilized substrates) or dietary approaches (reduction of substrate availability) represents pathogenetically grounded therapy. Temporal coupling is critical: physical activity should follow stress exposure or meals to consume mobilized substrates before they exert pathological effects. Time-restricted eating and avoidance of late-evening meals reduce substrate availability during circadian phases when utilization capacity is minimal. Conclusions: The FMC concept provides a novel integrative approach to understanding metabolic diseases as consequences of a mismatch between ancient physiology (a standardized regulatory–metabolic response inseparably linked with physical function) and modern conditions (psychoemotional stress without muscular work, dietary excess with sedentary lifestyle). Recognizing that regulatory activation invariably evokes standard metabolic mobilization, independently of functional need, explains why modern stressors become pathogenic. Restoration of functional–metabolic balance through targeted interventions may prevent or halt progression of metabolic diseases.